ANALISIS MISKONSEPSI SISWA KELAS IV PADA PEMBELAJARAN IPAS MELALUI METODE FOUR TIER DIAGNOSTIC TEST DI SD 7 BULUNGCANGKRING - Irawan Kurnianto; Fina Fakhriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Misconceptions are a common problem in IPAS learning at the elementary school level and can hinder students’ conceptual understanding and subsequent learning processes. This study aims to analyze the misconceptions of fourth-grade students in IPAS learning using the Four Tier Test method at SD 7 Bulungcangkring. The research employed a descriptive qualitative approach with fourth-grade students as the research subjects. Data were collected using a Four Tier diagnostic test consisting of four levels: multiple-choice answers, students’ confidence levels in their answers, reasons for selecting the answers, and confidence levels in the given reasons. This instrument was used to identify and distinguish students who correctly understood the concepts, those who lacked understanding, and those who experienced misconceptions. The results showed that students experienced misconceptions at varying levels, particularly in several basic IPAS concepts. These misconceptions were not only caused by a lack of conceptual understanding but were also influenced by incorrect prior knowledge and high confidence in incorrect answers. The Four Tier Test method proved to be effective in revealing students’ conceptual understanding in depth, as it was able to explore students’ reasoning and confidence levels simultaneously. The findings of this study are expected to serve as a reference for teachers in identifying misconceptions at an early stage and designing appropriate instructional strategies to improve students’ conceptual understanding in IPAS learning. Keywords: misconceptions, IPAS learning, Four Tier Test, elementary school students